Determination of Ground Water Quality for Agriculture and Drinking Purpose in Sindh, Pakistan - Benish Nawaz Merani; Saghir Ahmed Sheikh; Shafi Muhammad Nizamani; Aasia Akbar Panhwar; Mahvish Jabeen Channa (Journal of Pharmacy and Nutrition Sciences, 2014)
The study was conducted to assess the quality of ground water from different Talukas of district Tando Muhammad Khan for drinking and agriculture purpose. Water samples for determining the water quality were collected in one liter polyethylene bags by observing standard sample collection method. It was ensured that sample collection sites must be at least 500 feet away from each other.Physical and chemical parameters of ground and surface water samples such as pH, Electrical Conductivity (EC), Turbidity, Colour, Taste, Odour, Alkalinity as CaCO3, Bicarbonate (HCO3), Carbonate (CO3), Calcium (Ca), Magnesium (Mg), Hardness, Sodium (Na), Potassium (K), Chloride (Cl), Phosphate (PO4), Total Dissolved Solids (TDS) and Arsenic (As) were determined. The study clarified that pH and odour was within the permissible limits in majority of samples whereas, Arsenic (As),Hardness, Sodium (Na),Total Dissolved Solids (TDS), Taste, Chloride (Cl) and turbidity were beyond the permissible limits set by WHO. The groundwater status in Tando Muhammad Khan district, TDS in 50% samples, Chloride in 54.16% samples, Sulphate in 44.8% samples, Calcium in 38.5% samples, Sodium in 54.16% samples, hardness in 21.88% samples were beyond the WHO’s permissible limits for human consumption.